2019
DOI: 10.1002/art.40778
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Peripheral Subclinical Enthesopathy in Therapy‐Naive Patients Treated With Ustekinumab for Moderate‐to‐Severe Chronic Plaque Psoriasis: A Fifty‐Two–Week, Prospective, Open‐Label Feasibility Study

Abstract: Objective. To investigate whether sonographically determined subclinical enthesopathy in patients with moderateto-severe psoriasis regresses with the use of ustekinumab therapy for skin disease.Methods. Seventy-three patients with moderate-to-severe psoriasis, who were not treated with systemic therapy and did not have symptoms of psoriatic arthritis (PsA), and 23 healthy volunteers were screened by ultrasound for subclinical enthesitis. Subsequently, 23 patients with psoriasis whose ultrasound results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 17 publications
1
50
0
8
Order By: Relevance
“…Evidence supporting the reversal of existing damage and/or comorbid conditions caused by systemic inflammation in patients with psoriasis is encouraging but not as well developed as evidence supporting the first stated goal of preventing damage and preventing future comorbidities. A study of ustekinumab treatment in patients with moderate‐to‐severe psoriasis ( N = 46) showed regression of subclinical inflammatory entheseal and synovial abnormalities, suggesting the possibility that PsA development could be inhibited by biological treatment of psoriasis . Additionally, a study of 105 patients with varying degrees of psoriasis severity used CT angiography to show that treatment with systemic or biological agents was associated with improvement in noncalcified coronary plaque burden .…”
Section: Goals For Treating Systemic Inflammation In Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence supporting the reversal of existing damage and/or comorbid conditions caused by systemic inflammation in patients with psoriasis is encouraging but not as well developed as evidence supporting the first stated goal of preventing damage and preventing future comorbidities. A study of ustekinumab treatment in patients with moderate‐to‐severe psoriasis ( N = 46) showed regression of subclinical inflammatory entheseal and synovial abnormalities, suggesting the possibility that PsA development could be inhibited by biological treatment of psoriasis . Additionally, a study of 105 patients with varying degrees of psoriasis severity used CT angiography to show that treatment with systemic or biological agents was associated with improvement in noncalcified coronary plaque burden .…”
Section: Goals For Treating Systemic Inflammation In Psoriasismentioning
confidence: 99%
“…A study of ustekinumab treatment in patients with moderate-to-severe psoriasis (N = 46) showed regression of subclinical inflammatory entheseal and synovial abnormalities, suggesting the possibility that PsA development could be inhibited by biological treatment of psoriasis. 69 Additionally, a study of 105 patients with varying degrees of psoriasis severity used CT angiography to show that treatment with systemic or biological agents was associated with improvement in noncalcified coronary plaque burden. 70 Furthermore, a study of 53 patients with moderateto-severe psoriasis reported that methotrexate and ustekinumab significantly decreased carotid intima-media thickness levels.…”
Section: Goal 2: Reverse Existing Damage/comorbid Conditions Caused Bmentioning
confidence: 99%
“…The anatomical basis for joint pain in the preclinical phase of PsA is not yet understood, and musculoskeletal ultrasonography (US) could be a reliable modality to detect musculoskeletal inflammatory lesions in these patients with psoriasis 8–11. Moreover, this sonographic-determined inflammation appears to regress under systemic therapy for skin disease raising the possibility that skin-directed therapy may prevent arthritis development 12. However, the current inability to accurately enrich for imminent PsA means that the question of PsA prevention strategies remains in its infancy 13…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that nearly half of the patients with psoriasis screened using ultrasound have at least 1 inflammatory entheseal abnormality. 237 Within 12 weeks of treatment with the IL-12/IL-23 inhibitor (ustekinumab), the suppression of subclinical enthesopathy maintained through week 52 of therapy was evident. 237 This finding may support the pathogenic role of IL-23 mainly in the early phases of entheseal-associated disorders including PsA, AS, or other forms of SpA.…”
Section: Il-23 Targeting For Spa Disease Preventionmentioning
confidence: 99%
“…Of note, targeting IL‐23 in SpA seems to be more relevant in early stages of disease; thus, the implication of this therapy should be considered at early phases or even before clinical joint disease appearance such as in psoriasis to prevent the clinical entheseal PsA‐related disease manifestation. Recently, we have shown that nearly half of the patients with psoriasis screened using ultrasound have at least 1 inflammatory entheseal abnormality . Within 12 weeks of treatment with the IL‐12/IL‐23 inhibitor (ustekinumab), the suppression of subclinical enthesopathy maintained through week 52 of therapy was evident .…”
Section: Animal Models Showing a Role For Il‐23 In Enthesitismentioning
confidence: 99%